LAY OUT AND PRODUCTIVITY ANALYSIS OF LEMURU CANNING INDUSTRY IN BANYUWANGI, EAST JAVA - Febrianti, Desy; Perceka, Medal Lintas; Syah, Ardi Rahman (Universitas Mataram, 2025)
Layout design can determine how efficient and effective a production process is. The decision to election desain layout will have an impact on optimizing the factory area, determining the production equipment used, operational costs and the number of workers used. The research aim is to find out the type of layout applied in the production process, to know the basic considerations for choosing the layout, to know the material flow pattern, and to know the productivity of fish canning factories in Banyuwangi Regency. Data collection was carried out by directly observing the production process at two fish canning companies in Muncar District, Banyuwangi Regency, East Java. Observations were made on the arrangement of production departments/sections, the location of production equipment, material handling flow, and factory productivity. The data was analyzed in a comparative descriptive manner between the two companies. The research results show that both fish canning companies use a type of product layout, which is indicated by the arrangement of machines and production facilities which are arranged according to the production process flow using the machine after machine principle. The choice of layout type aims to reduce material movement, reduce cost, and make it easier to monitor production activities. Productivity analysis at both companies shows values above the standards set by the company. Recomended further research is an analysis of the economic efficiency of the layout and selection patterns of the selected materials.